Evaluation of Two Different Methods of Fulvic Acid Application (Seed Priming and Foliar Spray) on Growth, Yield, and Nutritional Quality of Pea (Pisum sativum L.) - Rehab M. Mahdy; Adel M. Al-Saif; Mohamed E. M. Ahmed; Tahany S. Abd El-Bary; Ashutosh Sharma; Abdel-Nasser A. El-Sheshtawy; Rasha S. El-Serafy; Tamer S. Abd El-Ghany (Plants, 2024)
Pea is a commercially significant legume that is widely utilized worldwide and has a elevated amount of nutrition and bioactive components. Its consumption is attributed to a number of health benefits and its potential as a functional food. Fulvic acid can be used as a bio-stimulant to promote plant growth and increase nutrient availability and uptake. A field experiment was designed during two subsequent cropping seasons (i.e., 2022–23 and 2023–24) to evaluate the impact of two methods of fulvic acid application of seed priming and foliar spray on the growth, yield, antioxidant content, and nutritional value of pea (Pisum sativum L.) plants. The seeds were primed with fulvic acid at 1.5, 3 g L−1, and water, while a foliar spray of fulvic acid with the same doses was performed on the seedlings of non-primed seeds. The results obtained exhibited that the seed priming technique with fulvic acid outperformed the fulvic acid foliar applications. The increase in the fulvic acid dose to 3 g L−1 in both application techniques exhibited the highest plant growth, heaviest fresh and dry weights, and highest green seed yield. The maximum growth parameters were recorded after the foliar spray treatment at a dose of 3 g L−1, as it led to improvement in the growth parameters, leaf pigments, and total carbohydrates. The highest number of seeds per pod, number of pods per plant, 100-seed weight, and seed yield were obtained by the seed priming technique. From the results obtained, it may be concluded that the application of fulvic acid at 3 g L−1 via the seed priming technique is beneficial for enhancing the productivity of peas.